Analysis of the Implementation of the Zoning System Program in Admission of New Students: Analisis Pelaksanaan Program Sistem Zonasi dalam Penerimaan Peserta Didik Baru - Anzaldi, Muzrima; Sukmana, Hendra (Indonesian Journal of Education Methods Development, 2022)
The implementation of the zoning system program is carried out for equitable education efforts. The analysis technique in this research is qualitative analysis, referring to the theory of Miles and Huberman. The results show that, the analysis of the implementation of the zoning system program in the acceptance of new students includes strengths starting with the existence of clear regulations contained in the regulation of the Minister of Education and Culture Number 14 of 2018 PPDB starting from elementary, junior high, high school and state vocational schools which carry out under control. local government, namely the implementation of the zoning system. There is a weakness in its implementation, namely where the distribution of public schools is not evenly distributed in each region. However, there is an opportunity for students whose homes are close to schools and are more likely to be accepted. In the challenges contained in the implementation of this zoning system program where the program will not run continuously. The impact in the implementation of this zoning system program is that teachers cannot see the quality of students, then it causes student achievement to decline and also triggers disappointment with parents of outstanding students who will register their children's schools to state schools.